The Rise and Fall of NMDA Antagonists for Ischemic Stroke - Hoyte, L.; Barber, P. A.; Buchan, A. M.; Hill, M. D. (Current Molecular Medicine, 2004)
It has long been accepted that high concentrations of glutamate can destroy neurons,and this is the basis of the theory of excitotoxicity during brain injury such as stroke.Glutamate N-methyl- D-aspartate (NMDA)receptor antagonists such as Selfotel,Aptiganel,Gavestinel and others failed to show neuroprotective efficacy in human clinical trials or produced intolerable central nervous system adverse effects.The failure of these agents has been attributed to poor studies in animal models and to poorly designed clinical trials.We also speculate that NMDA receptor anatagonism may have hindered endogenous mechanisms for neuronal survival and neuroregeneration.It remains to be proven in human stroke whether NMDA receptor antagonism can be neuroprotective.
Keywords: glutamate